On-line At-Risk Behaviour Analysis and Improvement System (e-ARBAIS) - A.M., Shariff; T.S., Keng (2008)

(untitled)
Behaviour-based safety (BBS) is a programme that has been implemented in many organizations to identify at-risk behaviour and to reduce the injury rate of their workers. The effectiveness of the BBS was proven with many companies recording a high percentage of reduction of injury rate, especially during the first year of implementation. However, the BBS process could be very labour intensive. It requires many observers to make the process effective. Much effort was required to train the employees to become the observers. Many organizations that attempted to obtain the benefits of BBS did not sustain comprehensive participation required in BBS-related activities. With this drawback, it calls for a simplified process that could achieve the same result as BBS. This study was intended to establish an alternative to the BBS, termed as On-line At-Risk Behaviour Analysis and Improvement System (e-ARBAIS). The e-ARBAIS utilizes computer technology to play a role in making the routine observation process more sustainable and hence instilling the habitual awareness through the cognitive psychology effect. A database was set up with the pre-programmed questions regarding at-risk behaviours in the organization. The employees then utilized the database to feedback their observations. Through this process, the traditionally tedious observations by trained observers as required in BBS were now done naturally by all respondents. From the collective feedback, at-risk behaviours can be easily identified in the organization. The HSE committee within the organization can thus take the appropriate action by reinforcing the safety regulations or safe practices to correct all the unsafe behaviours either by changing the design ("hardware"), system ("software") or training the employee ("human-ware"). This paper introduces the concept, framework and methodology of e-ARBAIS. A case study was conducted in X Company (not a true name as the permission to use their real name was not given). A prototype computer program based on e-ARBAIS was developed using Microsoft Excel, named as "1-min Observation" programme. A preliminary result based on 1-month data collection is highlighted in this paper. Based on this preliminary result, "1-min Observation" programme has received positive feedback from the management and employees of Company X. It was done with very small resources and thus saved time and money compared to the traditional BBS technique. The e-ARBAIS concept is workable and practical since it is easy to implement, collect data and correct unsafe behaviour. Some recommendations by the employees of Company X are presented in this paper to further improve the "1-min Observation" programme. The project at Company X is still in progress in order to see a long-term impact of this programme. The e-ARBAIS has shown its potential to reduce injury in the organization if implemented with a thorough plan and strong commitment from all levels. Â© 2007 Elsevier Ltd. All rights reserved.